Friday

April 25, 2014

April 25, 2014

Posted by **pooja** on Saturday, April 30, 2011 at 7:53am.

- maths -
**MathMate**, Saturday, April 30, 2011 at 9:43amExpand both sides using sum of angles formula:

cos(a+b)=cos(a)cos(b)-sin(a)sin(b)

cos(a-b)=cos(a)cos(b)+sin(a)sin(b)

Divide by cos(a) on both sides and solve for tan(a) to get:

tan(a)=cot(b)*(1-m)/(1+m)

Check me.

**Related Questions**

precalculus - For each of the following determine whether or not it is an ...

Trig - Given: cos u = 3/5; 0 < u < pi/2 cos v = 5/13; 3pi/2 < v < ...

Trigonometry desperate help, clueless girl here - 2. solve cos 2x-3sin x cos 2x...

trig - Show that 1-cos2A/Cos^2*A = tan^2*A 1-cos2A/Cos^2*A = [Cos^2(A) - Cos(2A...

Trigonometry - 1.Solve tan^2x + tan x – 1 = 0 for the principal value(s) to two ...

Trig. - sec^2xcotx-cotx=tanx (1/cos)^2 times (1/tan)-(1/tan)=tan (1/cos^2) times...

trigonometry hlp me - 6.Prove that tan y cos^2 y + sin^2y/sin y = cos y + sin y...

Mathematics - Trigonometric Identities - Let y represent theta Prove: 1 + 1/tan^...

TRIG - what is another form of: sin (A+B) sin (A-B)/ cos^2 A cos^2 B a) cos^2 A...

maths - Find the roots of z^6 + 1 and hence resolve z^6 + 1into read quadratic ...